IMPLEMENTASI PEMBELAJARAN PAI-BP ERA PANDEMI COVID-19 DI SEKOLAH DASAR KECAMATAN KUBUNG - Candra, Ali; Khairat, Annisaul (Institut Daarul Qur'an Jakarta, Indonesia, 2024)
The aim of this research is to determine the implementation of Islamic Religious Education and Character Learning, further briefly PAIBP, during the Covid-19 pandemic at the Kubung District Elementary School, Solok Regency. This type of research is a phenomenological type of qualitative research approach. To obtain data in this research, the techniques used were (1) Interviews (in-depth interviews) (2) Documentation. The research results show that at the implementation stage the media used for the bold method was the WhatsApp application. Meanwhile, for the Offline method, the media used are Student Worksheets (LKPD), Modules and Student Textbooks. The implementation of PAI-BP learning during the Covid-19 pandemic in Kubung District, Solok Regency was carried out using a Distance Learning or PJJ system using offline methods and a combination of dare and offline methods or what is known as e-blended learning with details of 70% choosing to carry it out. engagingly and 30% carry out e-blended learning.